Different monetary systems: Costs and benefits to whom? - José Luis Cordeiro (Universidad Central de Venezuela, 2003)
This paper analyzes the recent theoretical and practical evidence in terms of economic results of different exchange rate systems. It begins with a historical review and a summary of fixed versus flexible exchange rate systems. Then it compares the experiences of recent currency unions, mostly unilateral, and their relative economic performance during the recent currency crises in Latin America, East Asia and Eastern Europe. A set of issues is discussed in order to weigh the overall costs and benefits for several economies. These issues include exchange rates, GDP performance, inflation rates and foreign reserves. The case of Argentina is also considered sepa-rately, comparing mostly seigniorage costs and interest-rate savings. The benefits and costs of the producers (central banks/governments) and the consumers (citizens) of money are discussed separately. Free banking is also considered in a fast-changing world where there will probably be fewer but better currencies. Not just the euro is a reality now, but maybe the "amero" and the "worldo" or the "mondo" very soon.